Scaling Social Impact: Marketing to Grow Nonprofit Solutions. Issue 3 (July 2022) - Nardini, Gia; Bublitz, Melissa G.; Butler, Caitlin; Croom-Raley, Staci; Edson Escalas, Jennifer; Hansen, Jonathan; Peracchio, Laura A.
Nonprofit organizations addressing societal challenges such as hunger, poverty, and racial inequities want to grow the impact of their promising solutions to these problems—scaling social impact. Yet, local, community-based nonprofits often struggle to identify a path to scale their impact. To address this problem, the authors partnered with 11 nonprofits engaged in social impact scaling. By integrating insights on scaling from these nonprofit research partners together with academic research on scaling across a range of disciplines, they outline a framework for scaling community-based nonprofits and the marketing practices that support it. This research advances a two-stage social impact scaling framework termed "T-shaped Scaling." Within this framework, the vertical bar of the T refers to "scaling deep, " grounding solutions within a community, and the horizontal bar of the T represents "scaling wide, " adapting and transferring the scaled deep solutions to new communities. This framework advances both conceptual and practical understandings of social impact scaling. Finally, the authors explore the policy implications of social impact scaling and call on researchers in marketing to further investigate the scaling strategies and marketing practices that grow social impact.